Factors Affecting the Consumption of Fast Foods Among Women Based on the Social Cognitive Theory - Nooshin Beiranvandpour; Akram Karimi-Shahanjarini; Forouzan Rezapur-Shahkolai; Abbas Moghimbeigi (Hamadan University of Medical Sciences, 2014)
Introduction: Fast-food consumption among Iranian families appears to be increasing probably due to urbanization, popularization of western-style diets and increased women's labor force participation. Few theory-based investigations have assessed the determinants of fast food consumption. Therefore, the aim of this study was to determine the predictors of fast food consumption, based on the social cognitive theory (SCT) among women referred to health centers in Hamadan, West of Iran. Materials and Methods: This cross-sectional study was conducted using structured self-administered questionnaires on 384 women referred to 10 health centers in Hamadan city, Western of Iran. Health center was considered as a sampling unit and systematic random sampling method was applied to select health centers. Participants filled a questionnaire containing SCT constructs, an eight-item food frequency questionnaire, and demographic characteristics. Data was analyzed by independent T-test, one-way ANOVA, and multiple linear regression using SPSS-16. Results: The model could explain 21% of the variance in frequency of fast food consumption. Outcome expectations (p=0.04) and availability (p< 0.001) were the significant predictors. The career status of women was the only related demographic characteristic (p< 0.001). Conclusion: Interventions aimed to change outcome expectations and introducing nutritious alternatives to fast food could be promising to decrease the rate of fast-food consumption.